The Credibility of Nordic Exchange Rate Bands : 1987-1991 - Geadah, Sami (IMF Working Papers; Working Paper ;, 1992)
The credibility of the exchange rate bands in the Nordic countries during 1987-91 is examined with two tests. The results suggest that the credibility of Finland's exchange rate band within a twelve-month horizon could not be rejected except in the fall of 1991; however, the band lacked credibility within a five-year horizon throughout the period. Denmark's and Norway's bands lacked both short- and long-term credibility at the beginning of the period, but credibility could not be rejected from 1989 for Norway and as of 1990 for Denmark. The credibility of Sweden's band within a one-year horizon could not be rejected up to fall 1989, but thereafter its credibility deteriorated sharply.